The Role of HRM Practices in Predicting Faculty Turnover Intention: Empirical Evidence from Private Universities in Bangladesh - Joarder, Mohd. H. R.; Sharif, Dr. Mohmad Yazam (The South East Asian Journal of Management, 2011)
The present study was designed to examine the relationship between human resource management practices and turnover intention among the faculty members of private universities in Bangladesh. The prime objective of this study was to understand whether the institution’s HRM practices can influence faculty turnover decision. A total of 317 faculty members of different private universities located in Dhaka Metropolitan Area(DMA) participated in the survey and returned the questionnaire to the researchers which represented 57% response rate of the study. Multiple regression analyses were used to test the hypotheses of the study. The study found faculty compensation, supervisory support and job security as statistically significant predictors of faculty turnover intention. Therefore, privateuniversity management should pay much attention to this area of human resource practices (compensation, supervisory support, job security) to retain the potential faculty, thus reducing turnover intention. Limitations and suggestions for latest news headline are forwarded.